Perceived threat of COVID‐19, attitudes towards vaccination, and vaccine hesitancy: A prospective longitudinal study in the UK. Issue 4 (1st June 2022) - Phillips, Rhiannon; Gillespie, David; Hallingberg, Britt; Evans, Jennifer; Taiyari, Khadijeh; Torrens‐Burton, Anna; Cannings‐John, Rebecca; Williams, Denitza; Sheils, Elizabeth; Ashfield‐Watt, Pauline; Akbari, Ashley; Hughes, Kathryn; et al.
Abstract: Objectives: Using the Health Belief Model as a conceptual framework, we investigated the association between attitudes towards COVID‐19, COVID‐19 vaccinations, and vaccine hesitancy and change in these variables over a 9‐month period in a UK cohort. Methods: The COPE study cohort ( n  = 11, 113) was recruited via an online survey at enrolment in March/April 2020. The study was advertised via the HealthWise Wales research registry and social media. Follow‐up data were available for 6942 people at 3 months (June/July 2020) and 5037 at 12 months (March/April 2021) post‐enrolment. Measures included demographics, perceived threat of COVID‐19, perceived control, intention to accept or decline a COVID‐19 vaccination, and attitudes towards vaccination. Logistic regression models were fitted cross‐sectionally at 3 and 12 months to assess the association between motivational factors and vaccine hesitancy. Longitudinal changes in motivational variables for vaccine‐hesitant and non‐hesitant groups were examined using mixed‐effect analysis of variance models. Results: Fear of COVID‐19, perceived susceptibility to COVID‐19, and perceived personal control over COVID‐19 infection transmission decreased between the 3‐ and 12‐month surveys. Vaccine hesitancy at 12 months was independently associated with low fear of the disease and more negative attitudes towards COVID‐19 vaccination. Specific barriers to COVID‐19 vaccine uptake included concerns about safety and efficacy in light of its rapid development, mistrust of government and pharmaceutical companies, dislike of coercive policies, and perceived lack of relaxation in COVID‐19‐related restrictions as the vaccination programme progressed. Conclusions: Decreasing fear of COVID‐19, perceived susceptibility to the disease, and perceptions of personal control over reducing infection‐transmission may impact future COVID‐19 vaccination uptake.